2014
DOI: 10.4236/ojepi.2014.43021
|View full text |Cite
|
Sign up to set email alerts
|

Residual Risk of Transmission of HIV and Hepatitis B and C by Blood Transfusion in Bukavu in the Democratic Republic of Congo

Abstract: The aim of this study was to determine the incidence rates of HIV1/2 antibodies, HBV and HCV antibodies among voluntary blood donors and to estimate the residual risk of HIV, HBV and HCV infection among blood donors in Bukavu. We conducted a follow-up cohort study of volunteer blood donors who have made at least two blood donations in Bukavu (DRC) between January 2010 and December 2012. We recorded 2986 volunteer blood donors during the study period. The residual risk of viral transmission associated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
3
10
0
4
Order By: Relevance
“…The HIV seroprevalence of 1.15% detected among blood donors is indicative of low seroprevalence and decreased susceptibility to HIV infections. Similar studies in DRC reported similar result of 1.1% seroprevalence [ 7 ]. However, in Ethiopia, a relatively higher seroprevalence of 3.8% was reported [ 1 ].…”
Section: Main Textsupporting
confidence: 81%
See 1 more Smart Citation
“…The HIV seroprevalence of 1.15% detected among blood donors is indicative of low seroprevalence and decreased susceptibility to HIV infections. Similar studies in DRC reported similar result of 1.1% seroprevalence [ 7 ]. However, in Ethiopia, a relatively higher seroprevalence of 3.8% was reported [ 1 ].…”
Section: Main Textsupporting
confidence: 81%
“…Globally, about 1.6 million blood units are destroyed annually owing to TTIs seropositivity [ 5 ], with 10% discarded in sub-Saharan Africa [ 6 ]. In the neighbouring Democratic Republic of Congo (DRC), risk of transfusion-transmitted HIV, HBV and HCV was estimated at 0.6, 7.9 and 3.1 infections per 1000 donations, respectively [ 7 ]. Here in Kenya, an estimated risk of transfusion-transmitted HIV was reported at 2% [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Namekata et al observed that odds ratios of abnormally high CAVI scores in an association with diabetes after making adjustment for ages were 10.02 for men and 8.42 for women, compared with those who did not have diabetes [14]. In our recent study significant ORs of prediabetes and diabetes were observed in association with most CVD risk factors including age, hypertension, triglycerides ≥ 200 mg/dl and BMI ≥ 25 in both genders [19]. Our results imply much faster advancement of arteriosclerosis among persons both with prediabetes and with diabetes than in the normal persons.…”
Section: Discussionmentioning
confidence: 72%
“…Dans leur étude sur la prévalence et incidence du VIH et de l'hépatite B chez les donneurs de sang et sur l'estimation du risque résiduel de transmission du VIH et du virus VHB par la transfusion sanguine à Bukavu en 2009, Namululi et al avaient trouvé une incidence de 3,57/1000 personnes-années pour le VIH et 25,4/1000 personnes-année avec un risque résiduel de 0,22 et de 3,9 successivement pour les deux virus [ 2 ]. En 2014, dans cette même ville, Kabinda et al dans une étude sur les facteurs associés aux infections virales chez les donneurs de sang, avaient noté une prévalence de 4,8% d'hépatite B, 3,9% d'hépatite C et 1,6% de VIH chez les donneurs [ 4 ]. Ils avaient également retenu un risque résiduel de la transfusion sanguine de 0,6/1000 dons, 3,1/1000 dons, 7,9/1000 dons successivement pour le HIV, HCV et l'antigène HBs [ 4 ].…”
Section: Discussionunclassified
“…Parmi les causes de la non-sécurité de la transfusion sanguine en Afrique Subsaharienne, on cite le manque de ressources matérielles pour tester et conserver le sang et le manque des ressources humaines suffisamment formées pour bien réaliser les analyses biologiques [ 2 ]. Plusieurs études sur la transfusion sanguine montrent un important risque résiduel infectieux caractérisé par l'utilisation des tests incapables de déceler les anticorps des virus durant la période de séroconversion [ 1 - 4 ]. Après plusieurs dons sanguins, certains donneurs se voient être diagnostiqués séropositifs pour l'un ou l'autre marqueur infectieux.…”
Section: Introductionunclassified